Determinant of Indonesian Customers Intention to Use Islamic Life Insurance: Theory of Planned Behavior Approach - Khilmi, Slamet; Sunarsih, Sunarsih; Febriyanto, Ahmad; Yusro, Salma Nafisah Zulfa (EkBis: Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the determinants of intention to use Sharia life insurance among Muslims in Indonesia. The total sample size in this study reached 101 participants, determined using the convenience sampling technique. The data analysis technique employed in this research adopts partial least square structural equation modelling (PLS-SEM) using SmartPLS 3.0 software. The findings of this study indicate that the intention to use Sharia life insurance is determined by attitude and perceived behavioral control. However, religiosity was not found to mediate the relationship between attitude, perceived behavioral control, and subjective norm in relation to the intention to use Takaful. This research also provides recommendations for Sharia life insurance companies in Indonesia to enhance their products and services, aiming to foster a positive perception among the Muslim community towards Sharia life insurance.